Fasudil, a rho kinase inhibitor, limits motor neuron loss in experimental models of amyotrophic lateral sclerosis. (27th August 2013) - Takata, M; Tanaka, H; Kimura, M; Nagahara, Y; Tanaka, K; Kawasaki, K; Seto, M; Tsuruma, K; Shimazawa, M; Hara, H
<x xml:space="preserve">Abstract</x> Background and Purpose Amyotrophic lateral sclerosis (ALS) is a fatal neurodegenerative disorder with no effective treatment. Fasudil hydrochloride (fasudil), a potent rho kinase (ROCK) inhibitor, is useful for the treatment of ischaemic diseases. In previous reports, fasudil improved pathology in mouse models of Alzheimer's disease and spinal muscular atrophy, but there is no evidence in that it can affect ALS. We therefore investigated its effects on experimental models of ALS. Experimental Approach In mice motor neuron (NSC34) cells, the neuroprotective effect of hydroxyfasudil (M3), an active metabolite of fasudil, and its mechanism were evaluated. Moreover, the effects of fasudil, 30 and 100 mg·kg−1, administered via drinking water to mutant superoxide dismutase 1 (SOD1G93A) mice were tested by measuring motor performance, survival time and histological changes, and its mechanism investigated. Key Results M3 prevented motor neuron cell death induced by SOD1G93A. Furthermore, M3 suppressed both the increase in ROCK activity and phosphorylated phosphatase and tensin homologue deleted on chromosome 10 (PTEN), and the reduction in phosphorylated Akt induced by SOD1G93A. These effects of M3 were attenuated by treatment with a PI3K inhibitor (LY294002). Moreover, fasudil slowed disease progression, increased survival time and reduced motor neuron loss, in SOD1G93A mice. Fasudil also attenuated the increase in ROCK activity and PTEN, and the reduction in Akt in SOD1G93A mice. Conclusions and Implications These findings indicate that fasudil may be effective at suppressing motor neuron degeneration and symptom progression in ALS. Hence, fasudil may have potential as a therapeutic agent for ALS treatment.